Explaining Africa's (Dis)advantage - Harrison, Ann E.; Lin, Justin Yifu; Xu, L. Colin (World Bank, Washington, DC, 2013)
Africa's economic performance has been widely viewed with pessimism. In this paper, firm-level data for around 80 countries are used to examine formal firm performance. Without controls, manufacturing African firms perform significantly worse than firms in other regions. They have lower productivity levels and growth rates, export less, and have lower investment rates. Once geography, political competition and the business environment are controlled for, formal African firms lead in productivity levels and growth. Africa's conditional advantage is higher in low-tech than in high-tech manufacturing, and exists in manufacturing but not in services. The key factors explaining Africa's disadvantage at the firm level are lack of infrastructure, access to finance, and political competition.